10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Umbilical endometriosis is a rare extrapelvic manifestation of endometriosis, presenting diagnostic and surgical challenges. We report a case of a 43-year-old woman with a history of two cesarean sections who presented with a progressively enlarging, painful umbilical mass associated with cyclical symptoms and bloody discharge. The primary objective of this report is to highlight the diagnostic pitfalls and surgical decision-making in large umbilical endometriosis. Preoperative evaluation suggested an irreducible umbilical hernia. Surgical exploration revealed a large lesion extending to the fascia, which was completely excised and subsequently confirmed as umbilical endometriosis on histopathology. This case underscores the importance of including umbilical endometriosis in the differential diagnosis of umbilical masses in women of reproductive age.